Multisite calibration of a semi-distributed hydrologic and thermal model in a large Canadian watershed - Khorsandi, Mostafa; St-Hilaire, Andre; Arsenault, Richard (Hydrological Sciences Journal, 2022)

Regional estimation of river water temperature at ungauged locations - Ouarda, Taha B.M.J.; Charron, Christian; St-Hilaire, André (Journal of Hydrology X, 2022)
Keywords: Infolettre; Infolettre_Octobre_2022; Site_internet_RIISQ

A nested multivariate copula approach to hydrometeorological simulations of spring floods: the case of the Richelieu River (Québec, Canada) record flood - Saad, Christian; El Adlouni, Salaheddine; St-Hilaire, André; Gachon, Philippe (Stochastic Environmental Research and Risk Assessment, 2015)
Floods have potentially devastating consequences on populations, industries and environmental systems. They often result from a combination of effects from meteorological, physiographic and anthropogenic natures. The analysis of flood hazards under a multivariate perspective is primordial to evaluate several of the combined factors. This study analyzes spring flood-causing mechanisms in terms of the occurrence, frequency, duration and intensity of precipitation as well as temperature events and their combinations previous to and during floods using frequency analysis as well as a proposed multivariate copula approach along with hydrometeorological indices. This research was initiated over the Richelieu River watershed (Quebec, Canada), with a particular emphasis on the 2011 spring flood, constituting one of the most damaging events over the last century for this region. Although some work has already been conducted to determine certain causes of this record flood, the use of multivariate statistical analysis of hydrologic and meteorological events has not yet been explored. This study proposes a multivariate flood risk model based on fully nested Archimedean Frank and Clayton copulas in a hydrometeorological context. Several combinations of the 2011 Richelieu River flood-causing meteorological factors are determined by estimating joint and conditional return periods with the application of the proposed model in a trivariate case. The effects of the frequency of daily frost/thaw episodes in winter, the cumulative total precipitation fallen between the months of November and March and the 90th percentile of rainfall in spring on peak flow and flood duration are quantified, as these combined factors represent relevant drivers of this 2011 Richelieu River record flood. Multiple plausible and physically founded flood-causing scenarios are also analyzed to quantify various risks of inundation.
Keywords: Gachon_Philippe

The 2011 flood event in the Richelieu River basin: Causes, assessment and damages - Saad, Christian; St-Hilaire, André; Gachon, Philippe; El Adlouni, Salaheddine (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2016)
Keywords: Gachon_Philippe

Using the ERA5 and ERA5-Land reanalysis datasets for river water temperature modelling in a data-scarce region - Gatien, Philippe; Arsenault, Richard; Martel, Jean-Luc; St-Hilaire, André (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2023)

Coupling a peatland hydrological model with a snowmelt module in order to model the snowmelt runoff in a boreal ombrotrophic peatland in eastern Québec (Canada) - Riahi, Khawla; St-Hilaire, André; Bourgault, Marc-André; Taillardat, Pierre; Prijac, Antonin; Garneau, Michelle (Canadian Journal of Civil Engineering, 2024)
Peatlands are relatively common in the province of Quebec (Canada) where they occupy about 12% of the surface. The hydrology of peatlands remains insufficiently documented, more specifically during the spring period where data are currently lacking in many regions, including in the Quebec boreal territory. The paucity of spring data are due to snowmelt that causes flooding in peatlands and along rivers, which makes hydrometry complicated during this period of the year. In this paper, the Peatland Hydrological Impact Model (PHIM) was coupled with a snowmelt module (CemaNeige) to simulate spring flows in an ombrotrophic peatland located in the Romaine River watershed (Quebec). Discharge data from two summer seasons (2019 and 2020) were used to calibrate the hydrological model. Despite the relatively short time series, the results show a good performance. The simulated spring flows resulting from the PHIM + CemaNeige combination are of the right order of magnitude.
Keywords: Infolettre; Infolettre_Fevrier_2025

Quantifying the evolution of ensemble water temperature forecasts as a function of weather forecast lead-time: case study on the Nechako River watershed - Charles, Paul; Arsenault, Richard; Martel, Jean-Luc; Gatien, Philippe; St-Hilaire, André (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2023)

Future flow and water temperature scenarios in an impounded drainage basin: implications for summer flow and temperature management downstream of the dam - Khorsandi, Mostafa; St-Hilaire, André; Arsenault, Richard; Martel, Jean-Luc; Larabi, Samah; Schnorbus, Markus; Zwiers, Francis (Climatic Change, 2023)

Hydrothermal impacts of water release on early life stages of white sturgeon in the Nechako river, B.C. Canada - Oyinlola, Muhammed A.; Khorsandi, Mostafa; Penman, Rachael; Earhart, Madison L.; Arsenault, Richard; Brauner, Colin J.; St-Hilaire, Andre (Journal of Thermal Biology, 2023)